PENGGUNAAN MEDIA DIGITAL INTERAKTIF PADLET PADA KETERAMPILAN MENULIS DESKRIPSI DI KELAS IV UPT SDN 206 GRESIK - Fifi Aleyda Yahya; Rizka Nur Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the use of interactive digital media Padlet on descriptive writing skills in grade IV of UPT SDN 206 Gresik, and to determine the obstacles teachers face when implementing descriptive writing skills learning using interactive digital media Padlet. This study uses a qualitative approach with 23 research subjects in grade IV. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the use of interactive digital media Padlet can improve students' skills in learning to write descriptions. Students become more active in expressing ideas, composing sentences, choosing vocabulary, and composing descriptive paragraphs coherently. Of the 23 students, 16 students were able to write descriptive paragraphs according to the topic in the very good category, 12 students understood the paragraph structure well and correctly in the good category, and 10 students were able to use appropriate vocabulary in the fairly good category. In addition, Padlet facilitates collaborative learning through reading and commenting on friends' writing. Obstacles faced by teachers in using Padlet include limited internet network and low motivation for some students to learn to write descriptions. Overall, the interactive digital media Padlet is effective for learning to write descriptions and can be an alternative medium for learning Indonesian in elementary schools.